Frequency‐dependent and montage‐based differences in phosphene perception thresholds via transcranial alternating current stimulation. Issue 6 (23rd July 2019) - Evans, Ian D.; Palmisano, Stephen; Loughran, Sarah P.; Legros, Alexandre; Croft, Rodney J.
Abstract : It is well known that applying transcranial alternating current stimulation (tACS) to the scalp can generate artefactual visual perceptions of flashing or shimmering light known as phosphenes. The thresholds for generating these phosphenes have been used by international standards bodies to provide conservative estimates of the field strength required to interfere with human neural functioning and set safety limits accordingly. However, the precise relationship between electric currents and phosphene perception thresholds remains uncertain. The present study used tACS to systematically investigate the effects of the location and the frequency of stimulation on phosphene perception thresholds. These thresholds were obtained from 24 participants using a within‐subject design as a function of scalp stimulation sites (FPz‐Cz versus Oz‐Cz) and stimulation frequency (2–30 Hz in steps of 2 Hz). Phosphene perception thresholds were consistently lower for FPz‐Cz stimulation, and regardless of tACS location were lowest for 16 Hz stimulation. Threshold variation between participants was very small, which is meaningful when setting standards based on phosphenes. Bioelectromagnetics. 2019;40:365–374. © 2019 Bioelectromagnetics Society.